Proteolipid domains form in biomimetic and cardiac mitochondrial vesicles and are regulated by cardiolipin concentration but not monolyso-cardiolipin - Pennington, Edward Ross (J Biol Chem, 2018)
Cardiolipin (CL) is an anionic phospholipid mainly located in the inner mitochondrial membrane, where it helps regulate bioenergetics, membrane structure, and apoptosis. Localized, phase-segregated domains of CL are hypothesized to control mitochondrial inner membrane organization. However, the existence and underlying mechanisms regulating these mitochondrial domains are unclear. Here, we first isolated detergent-resistant cardiac mitochondrial membranes that have been reported to be CL-enriched domains. Experiments with different detergents yielded only nonspecific solubilization of mitochondrial phospholipids, suggesting that CL domains are not recoverable with detergents. Next, domain formation was investigated in biomimetic giant unilamellar vesicles (GUVs) and newly synthesized giant mitochondrial vesicles (GMVs) from mouse hearts. Confocal fluorescent imaging revealed that introduction of cytochrome c into membranes promotes macroscopic proteolipid domain formation associated with membrane morphological changes in both GUVs and GMVs. Domain organization was also investigated after lowering tetralinoleoyl-CL concentration and substitution with monolyso-CL, two common modifications observed in cardiac pathologies. Loss of tetralinoleoyl-CL decreased proteolipid domain formation in GUVs, because of a favorable Gibbs-free energy of lipid mixing, whereas addition of monolyso-CL had no effect on lipid mixing. Moreover, murine GMVs generated from cardiac acyl-CoA synthetase-1 knockouts, which have remodeled CL acyl chains, did not perturb proteolipid domains. Finally, lowering the tetralinoleoyl-CL content had a stronger influence on the oxidation status of cytochrome c than did incorporation of monolyso-CL. These results indicate that proteolipid domain formation in the cardiac mitochondrial inner membrane depends on tetralinoleoyl-CL concentration, driven by underlying lipid-mixing properties, but not the presence of monolyso-CL.